DEPREM TASARIM SINIFI 1 OLAN BETONARME BİNALARDA KONTROLLÜ HASAR PERFORMANS SEVİYESİ İÇİN GEREKLİ PERDE ALANININ ARAŞTIRILMASI - GENÇER, ŞEYMA GÜL (Fırat Üniveristesi, 2022)
Betonarme binaların depreme dayanıklı olarak tasarlanmasında perdeler önemli bir rol oynamaktadır. Aynı zamanda, betonarme binaların tasarım aşamasında Kontrollü Hasar Performans Hedefini sağlaması için gerekli perde alanının ne kadar olacağı konusu önemli bir belirsizlik problemi olmuştur. Bu nedenle farklı zemin grupları için betonarme binalarda gerekli minimum perde alanının belirlenmesi gerekmektedir. Bu tez çalışmasında, Türkiye Bina Deprem Yönetmeliği 2018' e göre Deprem Tasarım Sınıfı, 1 ve Bina Yükseklik Sınıfı, 4 olan betonarme bir binanın Kontrollü Hasar Performans Hedefini sağlaması için gerekli perde oranı araştırılmıştır. Söz konusu binanın zaman tanım alanında doğrusal olmayan analizleri dört farklı zemin grubu için elde edilmiş olup çözümler, HHT-? yöntemiyle hesaplanmıştır. Deprem etkisi olarak Türkiye Bina Deprem Yönetmeliği 2018' de belirtilen DD-2 seviyesine ait yatay spektrum ivme grafiği ile uyumlu A, B, C ve D grubu zeminler için üretilen 11 adet yapay deprem ivme kaydı kullanılmıştır. Viskoz sönümün etkisi, rijitlik orantılı olarak hesaba katılmıştır. Kolon, Kiriş ve Perde elemanların kesitlerine ait doğrusal olmayan davranış modeli için Kuvvete Dayalı Fiber (kesit hücresi/lif) eleman yöntemi seçilmiştir. Betonarme kesitlerde, sırasıyla beton için Mander, Priestly ve Park modeli, donatı için ise Menegotto-Pinto modeli kullanılmıştır. Sonuç olarak, A, B, C ve D grubu zeminlerde yer alan söz konusu binanın Kontrollü Hasar Performans Hedefini sağlaması için gerekli perde alanı oranları sırasıyla %0.75, %0.95, %2.30 ve %2.80 olarak belirlenmiştir.

Shear walls is an important role play in the earthquake-resistant design of reinforced concrete buildings. Furthermore, in the designing phase of reinforced concrete buildings, the issue of how much to require shear wall area for the Controlled Damage Performance Target has been an important uncertainty problem. For this reason, it is necessary to determine the minimum required shear wall area in reinforced concrete buildings for different soil classes. In this thesis, the required shear wall ratio for a reinforced concrete building with Earthquake Design Class, 1 and Building Height Class, 4 according to Turkey Building Earthquake Code 2018 to reach the Controlled Damage Performance Target is investigated. The nonlinear time history analyzes of the building are obtained for four different soil classes. The solutions are calculated by using the HHT-? method. As the earthquake effect, 11 artificial earthquake acceleration records produced for A, B, C, and D soil grades which are compatible with the horizontal spectrum acceleration graph of the DD-2 level specified in the Turkish Building Earthquake Code 2018, are used. The effect of viscous damping is taken into account with the stiffness proportional. The Force Based Fiber (section cell/fiber) element method is selected for the nonlinear behavior model of the cross-sections of the column, beam, and shear wall elements. In the reinforced concrete cross-sections, the Mander-Priestly-Park model is used for the concrete, and the Menegotto-Pinto model is used for the reinforcement bars, respectively. As a result, the required shear wall area ratios are determined as 0.75%, 0.95%, 2.30%, and 2.80%, respectively, for the building in A, B, C, and D soil classes to reach the Controlled Damage Performance Target.
Investigation of the required shear wall area for the controlled damage performance level in reinforced concrete buildings with earthquake design class 1
Keywords: İnşaat Mühendisliği